2023
DOI: 10.1101/2023.12.22.23300470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Generative Artificial Intelligence to Classify Primary Progressive Aphasia from Connected Speech

Neguine Rezaii,
Megan Quimby,
Bonnie Wong
et al.

Abstract: Neurodegenerative dementia syndromes, such as Primary Progressive Aphasias (PPA), have traditionally been diagnosed based in part on verbal and nonverbal cognitive profiles. Debate continues about whether PPA is best subdivided into three variants and also regarding the most distinctive linguistic features for classifying PPA variants. In this study, we harnessed the capabilities of artificial intelligence (AI) and natural language processing (NLP) to first perform unsupervised classification of concise, conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…This interpretation is consistent with the finding by Slegers et al, 2021 who reported verb frequency as a distinctive feature between amyloid positive and negative classes. 8 In our recent work, we also showed that verb frequency is a variable that significantly increases classification accuracy among the three variants of PPA 44 .…”
Section: Discussionmentioning
confidence: 76%
“…This interpretation is consistent with the finding by Slegers et al, 2021 who reported verb frequency as a distinctive feature between amyloid positive and negative classes. 8 In our recent work, we also showed that verb frequency is a variable that significantly increases classification accuracy among the three variants of PPA 44 .…”
Section: Discussionmentioning
confidence: 76%
“…We have previously provided a list of definitions and examples for features extracted from Stanza. 37 In addition to the Stanza-derived feature set, we included word length, sentence length, average log frequency of all words and content words, total number of sentences, total number of words, and syntax frequency. 35…”
Section: Methodsmentioning
confidence: 99%
“…English features a group of especially high-frequency verbs, such as "take" and "get," which may emerge as a distinct subset within the broader category of verbs upon cluster analyses based on frequency. 53 These high-frequency verbs possess abstract and flexible meanings as illustrated by phrases like "take a walk," "take a break," and "take a bath," which convey very distinct actions. 54,55 Conversely, in Persian, light verbs are more commonly integrated into complex verb structures rather than combined with independent noun phrases as in the English examples just mentioned.…”
Section: 46mentioning
confidence: 99%